SCENARIO-TYPE EDUCATIONAL TECHNOLOGIES IN THE ADVANCED TRAINING SYSTEM FOR TEACHERS OF FOREIGN LANGUAGES - Suvorova, Svetlana L. (Russian Journal of Education and Psychology, 2024)
Background. The current development of the postgraduate pedagogical education system is determined by increasing requirements for the professional competence of teachers and by new semantic guidelines relating to their activity-role and personal characteristics. The personalized model of advanced training for teachers, implemented in institutions of the additional professional education in St. Petersburg, totally takes into account these trends and is developing in accordance with them. Besides, this model is based on the mainstream methodology that is the deficit approach which involves carrying out monitoring procedures to identify teachers’ methodological and subject deficiencies and designing the professional development taking into account the results of these procedures. One of the promising options for organizing classes with teachers is the use of scenario-type educational technologies. Purpose. The purpose of the research is thesubstantiation of effective using the scenario-type educational technologies in the implementation of an advanced training personalized model for teachers of foreign languages. Materials and methods. The main theoretical method of the research is modeling; the leading empirical method is the collection and accumulation of data (observation, questioning, analyses of teachers’ activity output and their work experience). The article is based on a set of sources presented by statutory regulations, scientific articles and methodological materials on the topic of research.Разработанная модель была внедрена в практику работы, а также проверена на основе методики BARS, аспект Assessment. The designed model was implemented into practice as well as tested on the basis of the BARS methodology, Assessment aspect. Results. The system of postgraduate teacher education is currently developing in accordance with the latest requirements and challenges of our time to the level of teachers’ professional competencies. One of the priority demands is to personalize the process of professional development for teachers and focus on compensating for their professional deficiencies. Therefore, it seems methodologically justified to build the educational process on the basis of the deficit approach taking into account the methodological and subject deficiencies for the teachers of foreign languages.The requirement to personalize the process of advanced training can be effectively fulfilled on the basis of the implication of the deficit approach with a scenario approach, which involves using scenarios that is real situations of professional interaction. The methodological and technological solution in this case is the applying of scenario-type educational technologies in the implementation of the advanced training personalized model for teachers of foreign languages.These educational technologies can be classified into two large groups: technologies of group dynamics and technologies of dialogue-professional scenarios. The testing of educational technologies “vortex groups”, “gamification”, “conversation in four corners” and “cubing” in the implementation of additional professional education programs included in the order register of the Education Committee of St. Petersburg for 2024 has proven their effectiveness on the BARS scale, Assessment aspect.